Comparison of Medial and Dorsal Approach for Talonavicular Fusion: A Cadaver Study. Issue 1 (January 2022) - Patch, David A.; Andrews, Nicholas A.; Torrez, Timothy.; Sutherland, Charles R.; Harrelson, Whitt; Agarwal, Abhinav; Shah, Ashish
Category: Basic Sciences/Biologics; Hindfoot; Other Introduction/Purpose: Talonavicular (TN) joint arthrodesis is a common procedure for end stage arthritis. There are two common operative approaches used to expose the TN joint for articular preparation, the medial and dorsal. Classically, the medial approach has been the preferred method of TN joint fusion, but recent arguments have been made for the use of the dorsal approach. Articular surface preparation is a key tenant required for any joint fusion. To date no physical preparation studies have been done to compare the two approaches in terms of articular surface preparation. Methods: Ten fresh frozen cadaver specimens were obtained. Fluoroscopic radiographs were used to rule out any pre-existing pathology of the talonavicular joint. Specimens were assigned to receive either a dorsal or medial operative approach to the talonavicular joint. After joint preparation, the talonavicular joint was disarticulated and the amount of articular surface preparation was recorded using ImageJ software. Results: A total of 8 male and 2 female specimens were utilized with an average age of 64.5 +- 13.1. The dorsal approach had a higher average percentage of talar, navicular, and total talonavicular joint surface prepared. When examining joint surface area preparation regardless of approach used, the talar head was significantly less prepared than the navicular. The inter-observer correlation coefficient was excellent for both navicular and talar surface area prepared. Conclusion: The amount of articular surface preparation in the dorsal approach was consistently higher on average. Given the high rate of nonunion in isolated talonavicular and triple arthrodesis, surgeons should be aware that the dorsal approach may offer an increased amount of articular surface preparation. Our study adds to the growing body of evidence supporting the investigation and use of the dorsal approach when attempting talonavicular arthrodesis.